Inheritance of Mating Fators in Nocardial Recombinants - Brownell, George H. (1969)
The segregation of mating loci with other unselected genes was analyzed in recombinants obtained from matings of Nocardia canicruria and N. erythropolis. The loci C/c and E/e control nocardial compatibility. Four mating genotype combinations were observed: cE, Ce, CE, and ce. Strains of N. erythropolis bear the genotype cE and strains of N. canicruria bear the Ce alleles. The CE recombinant mating type is capable of mating with both organisms, whereas the ce-containing recombinant is nonfertile. The E locus was found to segregate with StrA1 (streptomycin-resistance gene) on the N. erythropolis linkage group. The C locus appeared linked to PurB2 (purine-requiring gene) on the N. canicruria linkage group. A few observed recombinants were capable of further segregation of unselected characters after colonial purification, suggesting a possible heterogenomic condition or multiple rounds of mating. Prior treatment of recombinants with acriflavine failed to alter their compatibility or the frequency at which recombinants were recovered. The segregation pattern of the mating loci allowed for specific recombinant class types to be compatible.